2020
DOI: 10.1111/rode.12720
|View full text |Cite
|
Sign up to set email alerts
|

Democracy in the neighborhood and foreign direct investment

Abstract: The determinants of foreign direct investment (FDI) have been extensively studied. Even though there is extensive research in the area, most of it is based on analyzing the effects of host country characteristics on FDI flows, and yet there is little research on how neighboring country characteristics play a role in facilitating FDI flows to host countries. This paper analyzes the association between the democracy level in neighboring countries and FDI flows to host countries. Using bilateral FDI flows from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…See, for instance, Dollar and Kraay (2003), Nunn (2007), Costinot (2009), andChor (2010) for further discussions. See, for example, Ferrantino (1993), Maskus and Penubarti (1995), Ma et al (2010), Feenstra et al (2013, and Sheng and Yang (2016) for more discussions on the relevance of economic institutions in trade, and Morrow et al (1998), Wong and Miaojie (2015), and Pinar and Stengos (2021) for the impact of political institutions on trade. Not coincidently, both the aspects of institutions are prominent factors shaping economic growth in the long term (see, e.g., Acemoglu et al, 2005a;Acemoglu & Johnson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…See, for instance, Dollar and Kraay (2003), Nunn (2007), Costinot (2009), andChor (2010) for further discussions. See, for example, Ferrantino (1993), Maskus and Penubarti (1995), Ma et al (2010), Feenstra et al (2013, and Sheng and Yang (2016) for more discussions on the relevance of economic institutions in trade, and Morrow et al (1998), Wong and Miaojie (2015), and Pinar and Stengos (2021) for the impact of political institutions on trade. Not coincidently, both the aspects of institutions are prominent factors shaping economic growth in the long term (see, e.g., Acemoglu et al, 2005a;Acemoglu & Johnson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Empirical findings have not reached a Corruption, democracy and the location decisions consensus either. While many studies report that democracies tend to be more appealing for FDI (Harms and Ursprung, 2002;Jensen, 2003;Busse, 2004;Ahlquist, 2006;Jakobsen and De Soysa, 2006;Jensen, 2008;Kolstad and Villanger, 2008;Choi, 2009;Doces, 2010;Doytch and Eren, 2012;Payton and Woo, 2014;Gossel, 2017;Pinar and Stengos, 2020;Zall e and Ou edraogo, 2021;Carril-Caccia et al, 2022), others have found that FDI is more inclined to invest in countries governed by autocratic regimes (Li and Resnick, 2003;Holmes et al, 2011;Arregle et al, 2013;Gani and Al-Abri, 2013;Mathur and Singh, 2013;Wright and Zhu, 2018). In addition, some studies have identified a non-significant relationship between foreign investment and regime type (Oneal, 1994;Yang, 2007;Ali et al, 2010;Kolstad and Wiig, 2012;Kerner, 2014;Chalmers and Mocker, 2017).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%